The Making of the American Calorie and the Metabolic Metrics of Empire (Journal of Transnational American Studies)
In “The Making of the American Calorie and the Metabolic Metrics of Empire,” Athia Choudhury develops a far-reaching critical genealogy of caloric biocitizenship that reframes her personal experiences with calorie counting and fat-phobic discourses that stigmatize the bodies and pleasures of racialized, working-class people, especially female bodied and fem-identifying people. Tracing practices of energy management and bodily discipline from colonial military outposts, nineteenth-century domestic manuals, dietetic discourses in the Philippines, and Native American Boarding Schools to a range of reform projects that framed calories as a tool for inculcating responsible eating through the domestic practices of white, bourgeois women, Choudhury highlights continuities between colonial subjection and modern biocitizenship, as well as the ways in which the putatively objective metric of the calorie positioned the New American Woman as a powerful catalyst for policing race in the intimate domain of the home.